USE OF POWERPOINT APPLICATIONS IN LEARNING ISLAMIC RELIGIOUS EDUCATION IN INCREASING STUDENT LEARNING MOTIVATION - Ahdar Ahdar; A. Fitri Nurhidayat; Musyarif Musyarif (Al-Irsyad: Journal of Education Science, 2023)
The nature of the training or the nature of teaching is influenced by several elements considering the impact of the level of learning on the school. One of the characteristics of the nature of learning can affect student achievement. The use of media in learning exercises can present a very beautiful learning atmosphere and can be used to increase the enthusiasm and inspiration of students' learning in utilizing the power point application media. This study aims to determine the focus of the use of power in learning Islamic Religious Education (PAI) and to increase student inspiration at SMP IT Wildan Mamuju. The type of research used is Classroom Action Research (CAR). This exploration area is located at SMP IT Wildan Mamuju with 10 students from class IX as the subject. The instrument used is a perception sheet that is linked to learning inspiration and a perception sheet about the application of control points. Then, the logical procedure used in this exploratory research is the strategy of examining observational information related to learning inspiration. From the consequences of the exams that have been described, it tends to be reasonable that the level of inspiration for the learning of class IX students towards PAI subjects has developed fundamentally from one cycle to another through the use of style points in developing experiences. The use of the power point application can increase the enthusiasm and learning inspiration for class IX students of SMP IT Wildan Mamuju.